Modifiable pre-natal risk factors for stillbirth in pregnant women of the Omusati Region, Namibia - Tshibumbu, Desire Dinzela (Stellenbosch : Stellenbosch University, 2017)
Thesis (MMed)--Stellenbosch University, 2016